Studi Literatur: Peran Fear of Missing Out dan Financial Technology dalam Mendorong Keputusan Investasi Generasi Z (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2026)
This study seeks to investigate the role of Fear of Missing Out (FOMO) and financial technology (fintech) in influencing Generation Z's investment decisions through a literature review approach. The rapid advancement of digital technology and the growing use of social media have transformed the financial behavior of young people, such that investment decisions are no longer solely based on rationality but are also shaped by psychological factors. The method used in this study is a literature review, which involves analyzing scientific articles indexed at both national and international levels published between 2021 and 2025. The findings indicate that FOMO can enhance investment participation, yet it also risks prompting impulsive and less rational decision-making. On the other hand, fintech contributes by simplifying access to financial services, improving transaction efficiency, and expanding financial inclusion. Nevertheless, real-time features on fintech platforms may amplify users' emotional responses, thereby magnifying the impact of FOMO. Accordingly, this research underscores the importance of financial literacy and prudent technology use to foster more rational investment decisions among Generation Z.